HMGB1 Protects the Heart Against Ischemia–Reperfusion Injury via PI3K/AkT Pathway-Mediated Upregulation of VEGF Expression - Zhou, Yan-Hong; Han, Qian-Feng; Gao, Lei; Sun, Ying; Tang, Zhan-Wei; Wang, Meng; Wang, Wei; Yao, Heng-Chen (Frontiers in Physiology, 2020)
Delivery of exogenous high mobility group box 1 (HMGB1) may exert a beneficial effect on myocardial ischemia–reperfusion (I/R) injury. Since the expression of vascular endothelial growth factor (VEGF) and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) in the myocardium mediates the cardioprotective function of basic fibroblast growth factor, we hypothesized that VEGF and the PI3K/Akt signaling pathway also mediate the protective effects of intravenously delivered HMGB1. Thus, the objective of the present study was to analyze the impact of intravenous administration of HMGB1 on the myocardial expression of VEGF, myocardial fibrosis, and cardiac function in rats subjected to acute myocardial I/R. The ischemia was induced by ligation of the left anterior descending coronary artery for 30 min and was followed by 3 h of reperfusion. Myocardial malondialdehyde content, infarct size, and collagen volume fraction decreased, while the activity of superoxide dismutase was increased, the expression of VEGF and p-Akt was upregulated, and cardiac function was improved in the HMGB1-treated group when compared with rats subjected to I/R only (all P < 0.05). However, these effects of HMGB1 were abolished by LY294002. The obtained results demonstrate that the cardioprotective effects of intravenous administration of HMGB1 prior to I/R may be mediated by upregulation of myocardial expression of VEGF, which may activate the PI3K/Akt signaling pathway.